Genotype × environment interaction: trade-offs between the agronomic performance and stability of durum (Triticum turgidum) wheat to stem-rust resistance in Kenya - Ogutu, Emmaculate A.; Madahana, Sammy L.; Bhavani, Sridhar; Macharia, Godwin (Frontiers in Plant Science, 2024)
Stem rust is a significant threat to production of durum wheat and frequently leads in substantial yield losses. It is important to understand the resistance mechanisms and stability of durum lines in stem rust-prone circumstances. This study utilized 7 × 7 alpha lattice design at the Kenya Agricultural and Livestock Research Organization, Njoro, to evaluate the stability and resistance of 49 durum genotypes across three seasons. We collected data on adult-plant resistance, disease progression using the final disease score (FDS) and area under the disease progress curve (AUDPC), and agronomic performance. Statistical analyses showed significant seasonal and genotypic effects on FDS, AUDPC, spike length, and grain yield (p≤0.01; p≤0.001), with notable genotype-by-season interactions impacting these traits (p≤0.05; p≤0.001). Broad-sense heritability estimates ranged from high (0.91 for AUDPC) to moderate (0.35 for kernels per spike), indicating genetic influences on these traits. Negative correlations between disease parameters and agronomic traits suggest potential trade-offs between resistance and agronomic characteristics. Genotype and genotype by environment (GGE) biplot analysis identified the first season (main season of 2019) as most critical for evaluating stem rust resistance. Durum lines G45, G68, G465, G487, G1196, and G1566 demonstrated consistent resistance across all seasons, proving their reliability. Additionally, GGE biplot analysis of yield highlighted G247, G59, and G13 as the highest yielding and most stable lines.The identification of these resistant and high-performing genotypes is vital for enhancing durum breeding programs, helping mitigate the impact of stem rust and improve overall yield performance.